The impact of financial reform on federal reserve autonomy - Bernard Shull (Levy Economics Institute of Bard College, 2012)
The Federal Reserve has been criticized for not preventing the risky behavior of large financial companies prior to the financial crisis of 2008-09, for approving mergers that aggravated the too big to fail problem, and for its substantial contribution to bailouts when their risk management failed. The Dodd-Frank Act of 2010, in attempting to diminish financial instability and eliminate too-big-to-fail policies, has established a new regulatory framework and laid out new responsibilities for the Federal Reserve. In doing so, it appears to address criticisms of the central bank by constricting its autonomy. The law, however, has also extended the Federal Reserve's supervisory authority and expanded its capacity to exercise regulatory control over its extended domain. This new authority is in addition to the augmentation of its monetary powers over the past several years. This paper reviews and evaluates both constraints imposed on the Federal Reserve by the Dodd-Frank Act and the expansion of Federal Reserve authority. It finds that the constraints are unlikely to have much impact, but the expansion of authority constitutes a significant increase in power and influence. The paper concludes that the expansion of Federal Reserve authority invites questions about the organizational design and governance of the central bank, and its traditional autonomy.
Keywords: G01; G28; 330; financial crisis; Federal Reserve; government policy and regulation